Analysing interaction behaviour in network supported collaborative learning environments: a holistic approach. (18th January 2008) - Petropoulou, Ourania; Lazakidou, Georgia; Retalis, Symeon; Vrasidas, Charalambos
In a Network Supported Collaborative Learning (NSCL) environment, the teacher needs to be able to conduct a similar analysis and learner evaluation as in traditional settings. However, recording, analysing and interpreting learners' interactions during a NSCL process is an open research issue. This paper proposes a conceptual framework for interaction analysis which is accompanied by a set of evaluation techniques such as descriptive statistics, log file analysis and social network analysis. Our main goal is the in-depth understanding of the nature of learners' interactions within NSCL environments in order to help teachers get a holistic picture of the learning process. We applied the proposed framework in a pilot study where primary school children attended a NSCL course on Mathematics in order to augment their self-regulative problem-solving skills. The findings from this study seem promising while at the same time new ideas for future work have arisen.